Nano-Technological Approaches to Improve the Efficiency of Bio-Assays - Shibsekhar Roy (Global Journal of Biotechnology and Biomaterial Science - Peertechz Publications, 2016)
One of the biggest issues in today's healthcare industry is to find a very fast yet effective diagnostic platform, which is suitable for our busy lifestyle  without  compromising  the  detection  efficiency.  The  major requirements of an efficient diagnostic platform can be summarized as minimum sample requirement, least reagent requirement, having options of multiple tests in a single platform, high through put analysis and last but never the least a non-expensive sample run. The largest contributor  of  the  bio-assay  industry  is  protein  based  chromogenic bio-assays,  which  depends  on  strong  antigen-antibody  interaction and  high  emissive  properties  of  reporter  dye  molecule  attached  to the antigen. In reality, this apparently simple looking reaction system has to face several difficulties before an appreciable signal is received by  the  photo-detector  to  give  an  analysable  dataset.  With  the  rapid emergence  of  nanotechnology  during  last  few  decades,  some  of  the critical  problems  have  been  solved  [1-5 ].  However,  a  large  number of  unresolved  issues  still  remain  there.  This  editorial  will  briefly address some of those critical issues and how they have been tackled by  nanotechnology.  The  two-most  tunable  variables  of  a  bio-assay platform  are  the  reporter  molecules  and  the  sensing  platform  as described by the Figure 1. We will describe both the issues separately in the next sections.